CDK11 Promotes Cytokine-Induced Apoptosis in Pancreatic Beta Cells Independently of Glucose Concentration and Is Regulated by Inflammation in the NOD Mouse Model - Sala, Ester; Vived, Celia; Luna, Júlia; Saavedra-Ávila, Noemí Alejandra; Sengupta, Upasana; Castaño, A. Raúl; Villar-Pazos, Sabrina; Haba, Laura; Verdaguer, Joan; Ropero, Ana B.; Stratmann, Thomas; Pizarro, Javier; et al. (Frontiers in Immunology, 2021)
Background: Pancreatic islets are exposed to strong pro-apoptotic stimuli: inflammation and hyperglycemia, during the progression of the autoimmune diabetes (T1D). We found that the Cdk11(Cyclin Dependent Kinase 11) is downregulated by inflammation in the T1D prone NOD (non-obese diabetic) mouse model. The aim of this study is to determine the role of CDK11 in the pathogenesis of T1D and to assess the hierarchical relationship between CDK11 and Cyclin D3 in beta cell viability, since Cyclin D3, a natural ligand for CDK11, promotes beta cell viability and fitness in front of glucose. Methods: We studied T1D pathogenesis in NOD mice hemideficient for CDK11 (N-HTZ), and, in N-HTZ deficient for Cyclin D3 (K11HTZ-D3KO), in comparison to their respective controls (N-WT and K11WT-D3KO). Moreover, we exposed pancreatic islets to either pro-inflammatory cytokines in the presence of increasing glucose concentrations, or Thapsigargin, an Endoplasmic Reticulum (ER)-stress inducing agent, and assessed apoptotic events. The expression of key ER-stress markers (Chop, Atf4 and Bip) was also determined. Results: N-HTZ mice were significantly protected against T1D, and NS-HTZ pancreatic islets exhibited an impaired sensitivity to cytokine-induced apoptosis, regardless of glucose concentration. However, thapsigargin-induced apoptosis was not altered. Furthermore, CDK11 hemideficiency did not attenuate the exacerbation of T1D caused by Cyclin D3 deficiency. Conclusions: This study is the first to report that CDK11 is repressed in T1D as a protection mechanism against inflammation-induced apoptosis, and suggests that CDK11 lies upstream Cyclin D3 signaling. We unveil the CDK11/Cyclin D3 tandem as a new potential intervention target in T1D.